A A Secure Quiz Management System with Dual Authentication for Pusat Tahfiz As Solihin - Zainal, Nabilah; Abd Warif, Nor Bakiah (Applied Information Technology And Computer Science, 2022)
A secure quiz management system for Pusat Tahfiz As Solihin is a web based system that allow quiz session held in virtually. An online quiz system or a web-based quiz system is one of the essential elements nowadays in the education industry. The main aim for developing this system is to ensure that the students of Pusat Tahfiz As Solihin can have a proper platform that are secure to answer a quiz session. Therefore, implementation of dual authentication security feature can improve the security level of the system. Email based OTP will be send to the user of the system for first time user and each time user login. Throughout the system, admin can do registration for admin, teacher, students and subject. Other than that, teacher can upload multiple choice question and students can answer the quiz that are uploaded by the teacher. At the end of this project, a secure quiz management system with dual authentication will be helpful to the school so that they can have the most convenient experience when taking quizzes using the system.